PENGARUH PENAMBAHAN DYNAMIC BALANCE TRAINING TERHADAP PENINGKATAN KELINCAHAN PEMAIN BASKET SMA NEGERI 1 WONOSARI KLATEN - Diana Putri Susanti; Nitaya Putri Nur Hidayati; Suhardi; Sugiono (Jurnal Nasional Fisioterapi, 2024)
Background: Basketball is a sport that requires high agility to be able to carry out the basic technical movements of the game, but the ability to change direction in basketball requires balance to be agile in changing the direction of movement. Thus, dynamic balance training are recommended as a means of injury prevention and prehabilitation. Therefore, apart from agility training, basketball players also need to do dynamic balance training. One of them is DBT. DBT is given because it increases the player's balance level through the musculoskeletal system which will facilitate neuromuscular ability, readiness and reactions. Objective: to determine the effect of adding DBT after routine training on increasing the agility of basketball players at State High School 1 Wonosari Klaten. Method This study used an experimental design with a randomized two groups pre and post test design conducted in September-October 2023. Subjects were basketball players at State High School 1 Wonosari Klaten who met the inclusion criteria. There were 15 subjects in the treatment group and 15 people in the control group. Agility was measured using the Agility T-Test at the beginning and end of the study. Results: Based on the results of the pre-post test statistics in the treatment group, a value of p=0.000 (p<0.05) was obtained, which means there is an influence. The results of the post test hypothesis test between the treatment group and the control group showed p=0.002 (p><0.05) which means there is an effect.><0.05) was obtained, which means there is an influence. The results of the post test hypothesis test between the treatment group and the control group showed p=0.002 (p<0.05) which means there isn an effect. Conclusion: additioning DBT after routine training has an effect on increasing agility in basketball players at State High School 1 Wonosari Klaten.